2018
DOI: 10.3389/fimmu.2017.01978
|View full text |Cite
|
Sign up to set email alerts
|

Human NF-κB1 Haploinsufficiency and Epstein–Barr Virus-Induced Disease—Molecular Mechanisms and Consequences

Abstract: Nuclear factor kappa-light-chain-enhancer of activated B cells 1 (NF-κB1)-related human primary immune deficiencies have initially been characterized as defining a subgroup of common variable immunodeficiencies (CVIDs), representing intrinsic B-cell disorders with antibody deficiency and recurrent infections of various kind. Recent evidence indicates that NF-κB1 haploinsufficiency underlies a variable type of combined immunodeficiency (CID) affecting both B and T lymphocyte compartments, with a broadened spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 90 publications
(171 reference statements)
0
13
0
Order By: Relevance
“…In a first step to understand the pathogenic potential of the identified NFKB1 sequence variants, Tuijnenburg et al 2 classified them into ''high-effect'' and ''moderate-effect'' variants according to probability predictions. Among the 13 high-effect variants, 10 mutations were predicted to cause expression of severely truncated nonfunctional proteins, which probably undergo rapid decay and thus cause p50 haploinsufficiency, in analogy with previous published NFKB1 mutations (as reviewed in Hoeger et al 1 ). Consistently, Western blotting showed reduced total amounts of wild-type p50 in patient-derived cells.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…In a first step to understand the pathogenic potential of the identified NFKB1 sequence variants, Tuijnenburg et al 2 classified them into ''high-effect'' and ''moderate-effect'' variants according to probability predictions. Among the 13 high-effect variants, 10 mutations were predicted to cause expression of severely truncated nonfunctional proteins, which probably undergo rapid decay and thus cause p50 haploinsufficiency, in analogy with previous published NFKB1 mutations (as reviewed in Hoeger et al 1 ). Consistently, Western blotting showed reduced total amounts of wild-type p50 in patient-derived cells.…”
mentioning
confidence: 59%
“…Consistent with previous reports, Tuijnenburg et al 2 observed a wide expressivity and highly variable penetrance associated with NFKB1 mutations. (as reviewed in Hoeger et al 1 ). Symptoms range from mild-to-severe immunophenotypic manifestations even within a single CVID family, but apparently asymptomatic mutation carriers are also common.…”
mentioning
confidence: 96%
“…In contrast to haploinsufficiency mutations, frameshift mutations in the central part of p105 (typically on the C-terminal side of the NLS), lead to skipping of the precursor stage and expression of p50-like mutant proteins as previously suggested (23, 32). The mutation (p.I567Nfs * 6) in Family D (S7) also predicts the expression of a p50-like protein, however with a molecular mass of ~89 kDa (which probably processed to p50) and which retains the NLS and translocates into the nucleus upon expression in HEK293T cells (Figure 3).…”
Section: Discussionmentioning
confidence: 91%
“…Importantly, monogenetic defects may represent distinct disease entities with particular phenotypes. Following identification in 2013 and 2015, heterozygous mutations in NFKB1 and NFKB2 now represent the largest CVID subgroups with known monogenetic mutations ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%